A novel LH2/GH2/battery multi-energy vehicle supply station using 100% local wind energy: Technical, economic and environmental perspectives. (1st May 2023) - Chen, Xiaoyuan; Pang, Zhou; Jiang, Shan; Zhang, Mingshun; Feng, Juan; Fu, Lin; Shen, Boyang
Abstract: With the gradual maturity of wind power technology, China's wind power generation has grown rapidly over the recent years. However, due to the on-site inconsumable electricity, the phenomenon of large-scale "wind curtailment" occurs in some areas. In this paper, a novel hybrid hydrogen/electricity refueling station is built near a wind farm, and a part of the surplus wind power is used to charge electric trucks, and the other part of the surplus power is used to produce "green hydrogen". According to real-time load changes, different amounts of liquid hydrogen and gas hydrogen can be properly coordinated to provide timely energy supply for hydrogen trucks. For a 400 MW wind farm in the western Inner Mongolia, China, the feasibility of the proposed system has been carried out based on the sensitivity and reliability analysis, the static and dynamic economic modeling, with an entire life cycle analysis. Compared to the conventional technology, the initial investment of the proposed scheme (700.07 M) decreases by 13.97%, and the dynamic payback period (10.93 years) decreases by 25.87%. During the life cycle of the proposed system, the accumulative NPV reaches 184.63 M, which increases by 3.14 times compared to the case by conventional wind technology. Highlights: A novel hybrid hydrogen/electricity refueling system to charge electric vehicles, and produce "green hydrogen". A realistic multi-energy study based on a 400 MW wind farm in western Inner Mongolia, China. Feasibility study with sensitivity and reliability analysis for the proposed system. Static and dynamic economic modeling on a hybrid hydrogen/electricity refueling station. The proposed system has technical and economic benefits, but much less carbon emissions.